Beyond the Fundamentals: How Media-Driven Narratives Influence Cross-Border Capital Flows - Isha Agarwal; Wentong Chen; Eswar Prasad (Institute of Labor Economics (IZA), 2024)
We provide the first empirical evidence on how media-driven narratives influence cross-border institutional investment flows. Applying natural language processing techniques to one-and-a-half million newspaper articles, we document substantial cross-country variation in sentiment and risk indices constructed from domestic media narratives about China in 15 countries. These narratives significantly affect portfolio flows, even after controlling for macroeconomic and financial fundamentals. This impact is smaller for investors with greater familiarity or private information about China and larger during periods of heightened uncertainty. Political and environmental narratives are as influential as economic narratives. Investors react more sharply to negative narratives than positive ones.
Keywords: F30; G11; G15; 330; media narratives; cross-border flows; institutional investors; portfolio investment in China; textual analysis; natural language processing